Demand for locally provided public services within the median voter's framework: The case of the Brazilian municipalities - Constantino Cronemberger Mendes; Maria da Conceiç\~ao Sampaio de Sousa (Institute for Applied Economic Research (ipea), 2015)
In this paper we estimated the demand for local public spending for the Brazilian municipalities within a median voter's framework. The median voter theorem provides a method of aggregating individual voter's demands to obtain community demand. The rationale for applying that framework came from the fact that in federal systems voter's preferences are more likely to be reflected at the local level as the consumers of public services have a better knowledge of the benefits and costs of the local public expenditures. Results obtained are consistent with the theoretical background thus suggesting that this hypothesis might be useful to describe the demand for local public goods in Brazil. In particular, the use of quantile regression permitted to investigate the impacts of the conditioning variables on local public expenses across different expenditures classes thus allowing for heterogeneity across municipalities. Our results also suggest that the impact of the city size on the quality of club goods shows crowding effects as g is between zero and one. However, in the estimated models, marginal congestion slightly decreases with expenditure. This is a rather surprising result as one is tempted to conclude that the congestion effect should be higher on big cities. Yet, a more careful look shows the drawbacks of such interpretation. The indivisibilities preclude the provision of certain services in small towns, concentrating their provision on larger cities. Hence, the higher expenditures of those big cities reflect not only a crowding cost but also the fact that these towns offer a wide range of services when compared to the small ones. So, in Brazil, contrary to the traditional results, the reduced congestion effect along the spending classes reflect the predominance of the scale elements measured by the population elasticities over the price effects.
Keywords: C5; C6; H4; H7; 330